Penerapan Metode Penemuan Terbimbing dengan Mengoptimalkan Penggunaan Lembar Kerja Siswa (LKS) Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VI SD Negeri 39 Mataram - Baiq Nurhayatun (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
The purpose of this study was to determine the increase in mathematics learning outcomes through the application of the guided discovery method by optimizing the use of student worksheets for Class VI students of SD Negeri 39 Mataram for the 2019/2020 academic year. This research is a classroom action research. The subjects in this study were 37 students of class VI SD Negeri 39 Mataram with 20 male students and 17 female students. Data collection techniques used were observation, documentation, and tests. Observation is used to collect interest in learning data. The test is used to measure learning achievement in Mathematics subjects. The data analysis used was descriptive qualitative and quantitative descriptive. The results showed that: Guided discovery method can improve mathematics learning outcomes of mixed arithmetic operation material in grade VI SD Negri 39 Mataram. Mathematics learning outcomes have increased with learning completeness 61.16% in the initial conditions to 78.38% in cycle I to 91.89% in cycle II classical student learning completeness has been achieved. From the increase in student activity, student activity increased from the acquisition score of 79.17% in cycle I, to 91.67% in cycle II. Based on data analysis, it was found that student activity in the learning process of Mathematics with the guided discovery method, the most dominant was working using tools / media, listening to / paying attention to teacher explanations, and discussions between students / between students and teachers. So it can be said that student activity can be categorized as active. Meanwhile, teacher activity increased from the acquisition score of 77.78% in the first cycle to 95.83% in the second cycle. For teacher activities during learning have implemented the steps of the guided discovery method by optimizing the use of student worksheets properly.